2014
DOI: 10.2174/138920291501140306113715
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus Erythematosus: Old and New Susceptibility Genes versus Clinical Manifestations

Abstract: Systemic Lupus Erythematosus (SLE) is one of the most relevant world-wide autoimmune disorders. The formation of autoantibodies and the deposition of antibody-containing immune complexes in blood vessels throughout the body is the main pathogenic mechanism of SLE leading to heterogeneous clinical manifestations and target tissue damage. The complexity of etiology and pathogenesis in SLE, enclosing genetic and environmental factors, apparently is one of the greatest challenges for both researchers and clinician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 157 publications
1
20
0
Order By: Relevance
“…Previous familial and twin studies on SLE reported several risk loci and genes including IRF5 , PTPN22 , CTLA4 , STAT4 , and BANK1 . In addition, our genetic study first presented GP96 as an SLE‐associated gene.…”
Section: Discussionsupporting
confidence: 52%
“…Previous familial and twin studies on SLE reported several risk loci and genes including IRF5 , PTPN22 , CTLA4 , STAT4 , and BANK1 . In addition, our genetic study first presented GP96 as an SLE‐associated gene.…”
Section: Discussionsupporting
confidence: 52%
“…These findings were corroborated in mice fed with HFD, observing that those animals that were treated with F. prausnitzii as a probiotic presented a lower hepatic lipid and lower plasma levels of liver transaminases (AST and ALT), suggesting a healthier liver than the one of the HFD counterpart mice (Table 1) [74]. Moreover, the presence of F. prausnitzii increases the expression levels of an inhibitor cell cycle progression, CDKN1A, which encodes for the p21 protein, whose levels are inversely associated with NAFLD progression and fibrosis [87]. Faecalbacterium prausnitzii is a butyrate-producing bacterium, from the Firmicutes phylum ( Figure 1) [84].…”
Section: Faecalbacterium Prausnitziimentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is one of the most relevant worldwide autoimmune disorders with a broad spectrum of autoimmune phenomena, clinical symptoms, and unknown etiology [1] SLE diverse presentations range from arthritis and malar rash through anemia and thrombocytopenia to nephritis, serositis, seizures, and psychosis [2] Complex interactions between environmental, genetic, and hormonal factors have been linked with the phenotype and progression of SLE [3] One such environmental factor is vitamin D, a steroid hormone recognized as essential for bone and mineral homeostasis. Sun exposure is the major source of vitamin D, but it is also available in some foods and supplements.…”
Section: Introductionmentioning
confidence: 99%